Physiological profile of elite Chinese female wrestlers - He, Z.-H.; Feng, L.-S.; Zhang, H.-J.; Xu, K.-Y.; Chi, F.-T.; Tao, D.-L.; Liu, M.-Y.; Lucia, A.; Fleck, S. J. (The Journal of Strength and Conditioning Research, 2013)
The purpose of this investigation was to describe the physiological profile of elite, senior Chinese female wrestlers. Twenty-five elite wrestlers, nationally ranked in the top 3 of their weight class, participated in this study. The subjects included Olympic and world champion medalists. The physiological profile included testing of running maximal oxygen consumption (VO2max), 3,200-m run time, 400-m run time, 30-second Wingate anaerobic power and capacity, shoulder, elbow, knee, and trunk isokinetic torque, and 1 repetition maximums (1RMs) in specified exercises. The major results (mean ± SD) were VO2max: 50.58 ± 3.33 ml/kg/min; 3,200-m run: 14 minutes 1 second ± 49 seconds; 400-m run: 1 minute 11 seconds ± 4 seconds; Wingate maximal anaerobic power: 495.21 ± 79.13 W and mean power: 262.97 ± 52.39 W; 1RM deadlift: 124 ± 19 kg; 1RM deep squat: 98 ± 11 kg; 1RM prone rowing: 72 ± 8 kg; 1RM power clean: 76 ± 12 kg; and 1RM hold and squat: 109 ± 17 kg. In absolute terms in the majority of measures, the heavier weight classes had greater values than the lighter weight classes, but relative to body mass, there were few differences in measures between the weight classes. The Olympic and World Championship medalist had the best value or was at the upper end of a measure's range for the strength and power measures. The results indicate that female wrestling success is not dependent on one physiological characteristic, but that a variety of physiological profiles can result in success. These data on elite female wrestlers can be compared with other wrestlers to help determine individual weaknesses or strengths and to design training programs that result in wrestling success.